Lung cancer combined with methotrexate-associated lymphoproliferative disorder: A case report - Sekimura, Atsushi (Int J Surg Case Rep, 2019)
INTRODUCTION: Methotrexate (MTX)-associated lymphoproliferative disorder occurs in rheumatoid arthritis patients treated with MTX; however, patients with concomitant pulmonary lesions are rare. We present a case of lung cancer combined with MTX-associated lymphoproliferative disorder for which, for which it was necessary to differentiate these from possible pulmonary metastasis. PRESENTATION OF A CASE: A 72-year-old man was referred to our hospital for treatment of squamous cell carcinoma in the left upper bronchus. He was receiving oral MTX and prednisolone for rheumatoid arthritis for 15 years. However, chest computed tomography performed 1 week before surgery revealed a 1-cm-sized pulmonary nodule in the right lung. Surgical pulmonary resection of the right lung tumor revealed substantial B-cell lymphoma-type lymphoproliferative disorder. Left upper lobectomy for the squamous cell carcinoma in the left upper bronchus was performed 5 weeks after the first surgery. Chest CT performed 2 weeks after the first surgery revealed a new 1-cm-sized nodule in the lower left lung lobe. However, after discontinuing oral MTX therapy, the new lesion in the left lower lobe disappeared. DISCUSSION AND CONCLUSION: In lung cancer patients treated with MTX for rheumatoid arthritis, MTX-associated lymphoproliferative disorder should be considered as a differential diagnosis.